Procédés interactifs de construction du sens dans le discours. Un modèle dans le développement des compétences orales au niveau avancé en langue étrangère ? - Wojciechowska, Bernadeta; Wilczyńska, Weronika (Studia Romanica Posnaniensia, 2017)
This article is aimed at giving a part of response when it comes to selecting resources, both relevant and easily accessible, which could serve as models in developing complex L2 oral competences. Those resources should encompass all levels (relational, semantic, and formal) required in realizing and interpreting efficiently our communicative intentions in oral language. Among suggested criteria, priority is clearly given to the mastery of interactive procedures in meaning construction, as playing a crucial role both in a speaker’s/learner’s communicative efficacy and the dynamics of his/her oral capacities’ development through the media. Moreover, to illustrate our reflection, we analyze the pedagogical and interactive potential in some excerpts from Le téléphone sonne, a radio segment available in podcast format.